United States : remarks on the Enterprise for the Americas Initiative [June 27, 1990 and September 4, 1990]. (1990)
Includes the statement by President Bush announcing the Initiative, and the remarks, message to Congress and fact sheet done when the legislative proposal was submitted to the Congress.
DC